Development Trend Physics Mobile Learning In 21St Century: A Systematic Literature Review - Sisda Ferlianti; Ridwan Efendi; Selly Feranie (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze the development of the design and implementation of mobile learning in physics learning. This research has been conducted via a systematic literature review research. The research subjects consisted of fifty journal articles selected from the Scopus Index database, Web of Science (WOS), Google Scholar, or ERIC from 2012 to 2022. The data have already been analyzed related to the year of publication, research objectives, and physics concepts used. The results of this study showed that the number of studies has increased over the years. In addition, the use of Physics Mobile Learning can have a positive impact on increasing students' various abilities. Most of the concepts that have been utilized are in the material of sound waves, Newton's laws, physical quantities and measurements, heat, momentum impulses, and gas laws. As a consequence, the learning media can be textbooks inter-actively. Thus, the development of Physics Mobile Learning needs to facilitate in complex and modern ways.